Results and Performance of the World Bank Group 2018 : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2019)
This report provides a retrospective assessment of the Bank Group’s results and performance acrossits project and program portfolio. This is relevant for understanding the stock of achievements to date and the foundations on which the Bank Group is delivering on the Forward Look and its ambitious capital package. The report synthesizes trends in Independent Evaluation Group (IEG) ratings and identifies explanatory factors behind portfolio performance. Each of the three Bank Group institutions assesses results differently because of their differing reporting periods, operating models, and clients. The supplementary file contains four appendixes and the remaining, more specialized topic appendixes of the Results and Performance of the World Bank Group (RAP) report. This report is IEG's annual review of the development effectiveness of the World Bank Group (WBG). The report synthesizes trends in ratings, and identifies explanatory factors behind portfolio performance. This report provides a retrospective assessment of the World Bank Group’s results and performance across its project and program portfolio. This is relevant for understanding the stock of achievements to date and the foundations on which the Bank Group is delivering on the Forward Look and its ambitious capital package. The four key appendixes for Results and Performance of the World Bank Group 2018 are included with the main file.